Implementation of Fuzzy Logic Method on Plantation Monitoring System in Website-Based Smart Farming - Oktariani, Clara; Nurdin, Ali; Handayani, Ade Silvia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The plantation sector is a crucial component of agriculture. However, plantation management faces several challenges, including limited technological integration within agriculture. The adoption of technology in plantations, particularly IoT (Internet of Things)-based monitoring systems, has become a significant trend in recent years. This system is designed to improve the efficiency of Smart Farming, allowing for more optimized management. This study implements the Fuzzy Logic method in a corn plantation monitoring system to address uncertainties and complexities in decision-making. The system integrates hardware and software, enabling real-time monitoring of environmental conditions through a web-based interface. Testing results indicate that the developed system achieves an accuracy level of 97.42%, providing valuable and responsive data to support farmers in decision-making. With this system, farmers can more effectively monitor and manage plantation conditions, potentially increasing productivity and agricultural yield quality.